2019
DOI: 10.5194/hess-23-1801-2019
|View full text |Cite
|
Sign up to set email alerts
|

Assessing the impact of resolution and soil datasets on flash-flood modelling

Abstract: Abstract. The present study assesses the impacts of two grid resolutions and the descriptors of soil texture and land cover on flash-flood modelling at local and basin scales. The ISBA-TOP coupled system, which is dedicated to Mediterranean flash-flood simulations, is used with two grid-cell sizes (300 and 1000 m), two soil texture datasets, and two land use databases to model 12 past flash-flood events in southeastern France. The skill of the hydrological simulations is assessed using conventional data (disch… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(12 citation statements)
references
References 60 publications
0
12
0
Order By: Relevance
“…It is widely recognized that different soil types have different properties (soil moisture, soil texture, and soil profile). Thus, the type of soil directly influences the formation of flash flood flow and its components (i.e., water, muds, and alluvial) [42]. In this study, thirteen soil types were observed in the study area, of which the Fa, Ha, and Fs soil types exceed 90% of the total area, followed by the Fj type and other soils (Figure 2b).…”
Section: Geologymentioning
confidence: 60%
“…It is widely recognized that different soil types have different properties (soil moisture, soil texture, and soil profile). Thus, the type of soil directly influences the formation of flash flood flow and its components (i.e., water, muds, and alluvial) [42]. In this study, thirteen soil types were observed in the study area, of which the Fa, Ha, and Fs soil types exceed 90% of the total area, followed by the Fj type and other soils (Figure 2b).…”
Section: Geologymentioning
confidence: 60%
“…The advantage of the LNP index is to give equal weight to the NSE values (first term), to the peak value estimation (second term) and to the timing of the peak simulation (third term). LNP appear to be a integrative criteria wellsuited for flash flood modelling (Lovat et al, 2019).…”
Section: Indicesmentioning
confidence: 99%
“…However, the question regarding how fine model resolutions should be, beyond the kilometre scale, in the so-called grey-zone (Barthlott and Hoose;2015) is still open. Several papers have found improvements from using model resolutions of 1.5 km or higher (Kendon et al, 2012;Martinet et al, 2017;Bonekamp et al, 2018 andLovat et al, 2019), whereas others found no significant gain (Chan et al, 2012;Panosetti et al, 2016;Lee et al, 2019). A possible reason is the fact that the appropriate settings for running current models at such high resolutions are not yet ready.…”
Section: Introductionmentioning
confidence: 99%